Akuntan Pendidik: Pengaruh Pengetahuan Terhadap Minat - Anita Anggraini (Eduka : Jurnal Pendidikan, Hukum, dan Bisnis, 2021)
ABSTRACTThis riset aims to determine how the relationship between knowledge about the duties and obligations of being an educational accountant with the interest in becoming an educational accountant, and how this level of knowledge can be used to predict how much interest someone has to become an educational accountant. accountant. This riset uses a quantitative approach with a survey method using a questionnaire as a research nstrument. The riset data were analyzed using simple regression with the condition that the data were interval scale and normally distributed. The results of this riset indicate that the higher the knowledge about the duties and obligations of being an educational accountant, the higher the interest in being an educational accountant with all its obligations, where 28.4% of the total interest in being an educational accountant is influenced by the magnitude of the knowledge score. And the amount of interest can be predicted by the regression equation: the amount of interest in a person to become an educational accountant = 23.343 + (0.533 x knowledge of the obligations of being an educational accountant).Keywords: educator accountants, knowledge, interestsABSTRAKRiset ini bertujuan untuk mengetahui bagaimana hubungan antara pengetahuan akan tugas dan kewajiban menjadi akuntan pendidik dengan minat untuk menjadi akuntan pendidik, dan bagaimana tingkat pengetahuan tersebut dapat digunakan untuk memprediksi seberapa besar minat seseorang untuk menjadi akuntan pendidik. Riset ini menggunakan pendekatan kuantitatif dengan metode survei dengan menggunakan angket sebagai instrumen penelitiannya. Data hasil riset dianalisis menggunakan regresi sederhana dengan syarat data berskala interval dan berdistribusi normal. Hasil riset ini menunjukkan bahwa semakin tinggi pengetahuan akan tugas dan kewajiban menjadi akuntan pendidik maka semakin tinggi pula minat untuk menjadi akuntan pendidik dengan segala kewajibannya, di mana sebesar 28,4% dari semua skor minat menjadi akuntan pendidik dipengaruhi oleh besarnya skor pengetahuan tersebut. Besarnya minat ini dapat diprediksi dengan persamaan regresi: besarnya minat seseorang menjadi akuntan pendidik = 23,343 + (0,533 x pengetahuan akan kewajiban menjadi akuntan pendidik).Kata kunci: akuntan pendidik, pengetahuan, minat